2021
DOI: 10.3390/vaccines9070738
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response to SARS-Cov-2 Vaccination in Liver Transplant Recipients–A Single-Center Experience

Abstract: Vaccination against SARS-CoV-2 infection is currently approved and shows favorable outcomes, but little known about antibody responses in solid organ transplant recipients, since these patients are known to have an impaired immune response upon vaccination and have not been included in admission studies. We therefore analyzed immunogenicity in 43 liver transplant (LT) recipients in a median of 15 days (IQR, 12–24) after receiving two doses of the mRNA-based SARS-CoV-2 vaccine BNT162b2 following the standard pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 21 publications
5
74
2
2
Order By: Relevance
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Solid organ transplant-specific treatments (calcineurin inhibitors, antimetabolites, corticosteroids) were often associated with a higher non-response rate or lower antibody titres [ 20 , 21 , 24 , 40 , 56 , 62 , 65 , 69 , 72 , 75 , 81 , 136 , [138] , [139] , [140] , [141] , [142] , 144 , 145 , 148 , [154] , [155] , [156] , [157] , 159 , 160 ] ( Table S5 ). Older age and lower estimated glomerular filtration rate were repeatedly associated with a non-responder status [ 21 , 24 , 79 , 120 , 138 , 142 , 144 , 155 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas several reports addressed the immunogenicity of the COVID-19 vaccines in solid organ transplant recipients, especially after kidney transplantation, data after hematopoietic stem cell transplantation are still scarce. It has been published that humoral [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] as well as cellular vaccination responses [ 12 , 14 , 16 ] were diminished after solid organ transplantation. A recent preprint publication described that in patients after heart and lung transplantation, baseline levels of activated PD-1+ HLA-DR+ CXCR5- CD4+ T cells (also known as T peripheral helper [T PH ] cells) and CD4+ T cells strongly predicted the ability to mount an antibody response against SARS-CoV-2 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, kidney transplant recipients (KTR) demonstrated a markedly impaired seroconversion rate of 40-60% after two doses of mRNA vaccines [7][8][9]. Liver, heart, and lung transplant recipients exhibited a reduced response to mRNA-based vaccines as well [10][11][12]. In a recently published study by Stumpf et al, KTR not only demonstrated a low humoral response following two doses of mRNA vaccines, but also displayed substantial impairment of the cellular response [13].…”
Section: Introductionmentioning
confidence: 99%